The Development of Ship Number Line Media for Improving Learning Outcomes of Integers Mixed Calculated Operating in Elementary School - Mahrani Mahrani (Universitas Tanjungpura, 2019)
This study aimed to describe the feasibility of a ship's number line media developed in integer operating material in class VI Elementary School, resulting in learning media in the form of a line number of vessels in integer counting operations in class VI Elementary School, describing how to apply ship number line media in operating material counting mixed integers in class VI Elementary School; and describe the improvement of student learning outcomes in calculating integer operating material after using ship number line media in class VI of Elementary School. Data collection techniques in the form of questionnaires were analyzed. The development research method or model used in this study was a 4-D model (Define, Design, Develop, Disseminate) that has been adapted, namely with the following stages of development research (1) product discovery, (2) product manufacture, (3 ) product development and (4) product dissemination. Based on the results of validation and dissemination, the shipyard media in mathematics learning developed by researchers was very feasible to use in the mathematics learning process in elementary schools or equivalent, because it had an average quality of 4.4 on a scale of 1-5 or (87%).